Optimized and Validated RP-UPLC Method for the Determination of Losartan Potassium and Chlorthalidone in Pharmaceutical Formulations - Tadiboyina Sirisha; Bannimath Gurupadayya; Sridhar Siddiraju (Tabriz University of Medical Sciences, 2015)
Purpose: A validated ultra performance liquid chromatography (UPLC) method has been developed and validated for the simultaneous determination of losartan potassium and chlorthalidone in pharmaceutical preparations. Methods: Waters-Acquity UPLC system equipped with Auto Sampler, PDA detector and operated with Empower-2 software was used for the present study. Detection was done at wavelength of 230 nm, HSS C18, 100 mm x 2.1x 1.8 μm column with a reverse phase elution and mobile phase composed of A and B mixed in the ratio 56:44 v/v (Where mobile phase A consists of potassium dihydrogen phosphate buffer of pH 3.0 and Mobile phase B consists of acetonitrile and methanol mixed in the ratio of 90:10 v/v) used at a flow rate of 0.4ml per minute. Results: The retention times for losartan potassium and chlorthalidone were observed at 0.72 and 1.89 minutes. The developed method was validated as per ICH guidelines. Linearity ranges were found to be 12.5-125 μg/ml and 3.125-31.25 μg/ml for losartan potassium and chlorthalidone, respectively. Conclusion: This method is fast, accurate, precise and sensitive hence it can be employed for routine quality control of tablets containing both drugs in industries.